Islam, colonialism and the modern age in the Netherlands East Indies : a biography of Sayyid ʻUthman (1822-1914) - Kaptein, N. J. G. (Brill's Southeast Asian library., 2014)
In this biography Nico J.G. Kaptein studies the life and times of Sayyid ʻUthman (1822-1914), the most prominent Muslim scholar of his time in the Netherlands East Indies.